Polyarteritis Nodosa and Bronchiolitis Obliterans with Organizing Pneumonia, an Unusual Association - Kaberi Dasgupta; A Kevin Watters; Arnold Zidulka (Canadian Respiratory Journal)
Bronchiolitis obliterans and organizing pneumonia (BOOP) is an inflammatory, fibrotic disorder of the small airways, alveoli and pulmonary intersitium. Often idiopathic and usually benign, this condition may cause dyspnea and influenza-like symptoms. Polyarteritis nodosa (PAN) is a small and medium vessel vasculitis, which usually involves the kidney and other viscera but rarely results in vasculitis of the lungs. This is the second case of BOOP associated with PAN reported in the literature. Knowledge of this association is likely to be of value because an undiagnosed vasculitis can rapidly become fatal.